2010
DOI: 10.1007/s12098-010-0352-2
|View full text |Cite
|
Sign up to set email alerts
|

Supportive Care of A Critically Ill Child

Abstract: The goal of pediatric intensive care is early identification, severity assessment and resuscitation of critical patients by utilizing standardized protocols. The primary or precipitating disorder should be the focus of attention and specific intervention. But in order to provide holistic care to a patient, due attention should also be rendered to supportive care. Monitoring of sick children in PICU is an essential part of management. Various monitoring technologies add to the clinical monitoring but cannot rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
2
0
3
Order By: Relevance
“…We assessed anthropometric indices BMI, weight, and height simultaneously; downward trends of which are favorable with chemical results and corroborative of nutritional status worsening in our patients. It has been shown that regular measurement of malnutrition in child critically ill patients is necessary to remain healthy ( 15 ). A study on ICU patients released by Azad et al conducted in 2011 showed similar results as ours; their patients needed nutritional support, too ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…We assessed anthropometric indices BMI, weight, and height simultaneously; downward trends of which are favorable with chemical results and corroborative of nutritional status worsening in our patients. It has been shown that regular measurement of malnutrition in child critically ill patients is necessary to remain healthy ( 15 ). A study on ICU patients released by Azad et al conducted in 2011 showed similar results as ours; their patients needed nutritional support, too ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged immobility due to chronic encephalopathy predisposes patients to pressure sores. Daily assessment of indwelling catheters is vital to prevent health-care-associated infections 17 .…”
Section: Correspondencementioning
confidence: 99%
“…Dennoch gibt es inzwischen deutlich strengere Empfehlungen als vor 2001 zur Begrenzung des Blutglukosespiegels bei Intensivpatienten: Die Werte sollten zwischen 80 -180 mg/ dl (4,4 -10 mmol/L) liegen [27]. Bei Kindern sollte ein Wert von 150 mg/dl (8,3 mmol/L) nicht überschritten werden [28] (▶ Abb. 2).…”
Section: Merkeunclassified